Training of Table Tennis Referees at Regional Level and West Java Province Level - Indra Safari; Rukmana, Anin; Inriyana, Ria; Inriyana, Tedi Supriyadi; Inriyana, Finny Rohaeni (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
The role of sport is very important for human life. So that sport can be used as a medium for refreshing and recreation, and also improve the economy, health, culture, and to achieve an achievement for someone who takes it. Many events or championships, especially table tennis championships, certainly require a referee who has knowledge and insight relevant to their field of expertise so that the match can be fair play. Therefore, this service aims to improve the understanding and skills of a referee, especially table tennis, in developing and organizing potential table tennis referees regarding table tennis management and to uphold a high attitude of sportsmanship in the implementation of events. With this activity, it is a solution to uphold sportsmanship in table tennis championship matches. Keyword: Sports, Training, Refereeing